The Optimum Conditions for Production of Soya Peptone by Acidic Hydrolysis of Soya Proteins - A. G. AL-Bahri, Mohammed B.; AL-Naimi, Safa A.; Ahammed, Sundus H. (Al-Khwarizmi Engineering Journal, 2009)
This study was carried out to obtain the optimum conditions necessary for the process of soya protein hydrolysis by using hydrochloric acid (as a chemical catalyst) instead of the papain enzyme (as a biological catalyst), for the production of soya peptone. These conditions are implemented to test the effect of the variables of the process of hydrolysis on the nature and quality of the product.        The production of soya peptone was studied for their importance in the process of preparing and producing the culture media used in medical and microbiological laboratories.      The process of production of soya peptone includes four main stages:Preparing the defatted soya flour, firstly.The soya protein hydrolysis, secondly.Purifying the product, thirdly , and then,Drying the product, finally.      By following the procedure of the present study, the optimum conditions for the process of soya proteins hydrolysis have been reached in present study are:Optimum concentration for the hydrochloric acid solution is 1N.Optimum hydrolysis process temperature ranged between 50-53°Optimum period of hydrolysis time ranged between 17.189-19.97 hr.      The productivity of soya peptone was 38.071%, by following the procedure and the optimum production conditions of the present study.